Which factors engage women in deprived neighbourhoods to participate in exercise referral schemes? - Nierkens Vera; Absalah Saida; Schmidt Melanie; Stronks Karien (BMC, 2008)
Abstract Background Exercise referral schemes (ERS) have become a popular way of promoting physical activity. The aim of these schemes is to encourage high risk patients to exercise. In evaluating these schemes, little attention has been paid to lower socio-economic groups in a multi-ethnic urban setting. This study aimed to explore the socio-demographic and psychosocial characteristics of female participants in ERS located in deprived neighbourhoods. The second aim was to determine which elements of the intervention make it appealing to participate in the scheme. Methods A mixed method approach was utilized, combining a cross-sectional descriptive study and a qualitative component. In the quantitative part of the study, all female participants (n = 523) filled out a registration form containing questions about socio-demographic and psychosocial characteristics. Height and weight were also measured. In the qualitative part of the study, 38 of these 523 participants were interviewed. Results The majority of the participants had a migrant background, a low level of education, no paid job and a high body mass index. Although most participants were living sedentary lives, at intake they were quite motivated to start exercising. The ERS appealed to them because of its specific elements: facilitating role of the health professional, supportive environment, financial incentive, supervision and neighbourhood setting. Conclusion This study supports the idea that ERS interventions appeal to women from lower socio-economic groups, including ethnic minorities. The ERS seems to meet their contextual, economic and cultural needs. Since the elements that enabled the women to start exercising are specific to this ERS, we should become aware of whether this population continues to exercise after the end of the scheme.